Perioperative intravenous paracetamol as adjunctive treatment for postoperative pain relief after orthopaedic surgery involving lower limb bone fracture - Muda, Mohd Izwan Azmi (2016)
Backgraound: Perioperative intravenous paracetamol has been shown to reduce postoperative pain scores and morphine consumption in certain surgical populations. We studied the effects of perioperative intravenous paracetamol on postoperative pain relief among patients undergoing orthopaedic surgery for lower limb bone fractures. Our primary end points were a reduction in postoperative pain score and cumulative morphine consumption 6 hours postoperatively Methods: 62 patients undergoing orthopaedic surgery involving lower limb bone fractures that fulfilled inclusion and exclusion criteria were recruited in Hospital Universiti Sains Malaysia and randomized into two groups. The intravenous paracetamol group (n = 31) received intravenous paracetamol 1 gram (100 ml) at skin closure while the placebo group (n = 31) received intravenous normal saline (100 ml) at skin closure. Both groups received a standardized regimen of general anaesthesia and were given intravenous morphine postoperatively via a Patient Controlled Analgesia Device. Postoperative pain score, cumulative morphine consumption and side effects were recorded using a visual analogue scale at 30 minutes, 3 and 6 hours postoperatively. Results: The mean pain scores were significantly lower in intravenous paracetamol group compare to placebo group in resting (mean ± SD = 4.23 ± 1.63 VS 5.42 ± 2.41 at 30 min, p = 0.015; 2.81 ± 1.58 VS 4.19 ± 2.09 at 3 hours, p = 0.005; 2.23 ± 1.20 VS 3.23 ± 1.86 at 6 hours, p = 0.015) and moving (mean ± SD = 6.45 ± 1.69 VS 7.26 ± 2.21 at 30 min, p = 0.111; 5.00 ± 1.79 VS 6.48 ± 1.86 at 3 hours, p = 0.002; 4.35 ± 1.38 VS 5.35 ± 1.70 at 6 hours, p = 0.014). There were no significant different in cumulative morphine consumption between intravenous paracetamol and placebo group despite total cumulative morphine consumption for intravenous paracetamol group was lower than placebo group (mean ± SD = 14.65 ± 10.12 VS 20.61 ± 14.33, p = 0.063). Incidence of side effects was similar between the two groups. Conclusion: This study show beneficial effects of perioperative intravenous paracetamol as part of multimodal analgesia for patients who have lower limb bone fractures going for orthopaedic procedures. We recommended the use of intravenous paracetamol as part of multimodal analgesia in treating postoperative pain.